The world during the COVID-19 pandemic: Remote work and virtual teams in Georgia (Economic and Political Thought, 2020)
The nature of work in today’s organisations is becoming more and more complex, dynamic, and global. Nowadays, remote work and virtual teams have become a vital component of modern corporate organisations. The goal of the research is to examine some of the main problems that the Georgian public or private sector’s remote employees have faced. The main purpose of the paper is to determine the current remote work situation of the public or private sector employees in Georgia in accordance with the restrictions adopted by the country in order to reduce the threat of the coronavirus spread. In addition, the research seeks to identify and examine the factors that influence employees’ remote work effectiveness and to determine under what conditions remote work and virtual teams can be a worthwhile investment in a public or private organization. Studies have shown that employees doing remote work in Georgia face challenges, such as: increased working time, unfair redistribution of functions and duties, performed work quality control, internet problems, access to the organizational systems, lack of necessary technical inventory, unproductiveness and lack of face-to-face communication. Methodologically, the work is based on the analysis of available literature and the results of the statistical research based on the survey of 187 respondents, a random sample of different Georgian private and public sector employees. Consequently, managers should be aware of modern communication, technology and leadership methods that can be used in effective and efficient way to increase the virtual work quality. The article concludes that both the technological and the organisational approaches need to be addressed in parallel in order to work effectively.
Keywords: remote work; virtual teams; technology; tools; communication; leadership; trust building